Effects of high-temperature cooking on the gamma-aminobutyric acid content and antioxidant capacity of germinated brown rice (Oryza sativa L.). Issue 1 (1st January 2021) - Toyoizumi, Tomoyasu; Kosugi, Toru; Toyama, Yusuke; Nakajima, Teruko
ABSTRACT: Germinated brown rice (GBR) has a high gamma-aminobutyric acid (GABA) content and antioxidant capacity; however, the effects of high-temperature cooking on these characteristics are unclear. We investigated alterations in GABA content, antioxidant capacity, 15 proteinogenic amino acids, TP and reducing sugar content, and color of cooked GBR at 105°C to 135°C and at different times (40 to 90 min) at 105°C. The contents of GABA and 9 proteinogenic amino acids decreased via thermal decomposition with increasing cooking temperatures. The hydrophilic and lipophilic antioxidant capacities (DPPH and L-ORAC) were enhanced at temperatures >125°C. L-ORAC values were strongly associated with the glucose content and L*, a *, and b * values. Additionally, prolonged treatment time decreased the content of 12 amino acids but increased DPPH and L-ORAC. Our results on functional ingredients and activity are useful for both home cooking and manufacturing processes and may lead to the development of better-processed products.